(untitled) (Tabularium Historiae, 2020)
The article tries to reconstruct the processes inside the Bydgoszcz society in the period before the city’s incorporation into the Republic of Poland on 22 January 1920. Contrary to popular opinion, it was not the ethnic structure or the national movement and internal political actions what decided about the change of the city’s belonging, but global political processes. The society of Bydgoszcz city, both in the Polish, German and Jewish segments, adapted to these decisions, on the basis of legalism and realism. The typical pax urbana was preserved.